Anticardiolipin antibodies in HIV infection: association with cerebral perfusion defects as detected by 99mTc-HMPAO SPECT. - Rubbert, A (1994)
Anticardiolipin antibodies (ACA) belong to a heterogeneous group of antibodies directed against negatively charged phospholipids. In patients with rheumatic disorders, their presence has been correlated to the occurrence of thromboembolic complications, thrombocytopenia, abortions and other disease manifestations. Several studies have revealed the detection of mostly high-titre ACA in a significant proportion of HIV-infected patients without any known clinical relationship. In our study, ACA were detected in 17/34 HIV-infected patients, and their presence was significantly associated with the detection of cerebral perfusion abnormalities by 99mTc-HMPAO SPECT. SPECT scans were classified as normal or as focal or diffuse defects in uptake. Most patients (13/16) with cerebral perfusion defects had elevated ACA titres in contrast to 4/18 patients with normal SPECT findings (P = 0.002). Focal uptake defects were always associated with the presence of ACA. No correlation to clinical features or other laboratory parameters was evident. Our results suggest a possible implication of autoimmune mechanisms in the pathogenesis of cerebral perfusion abnormalities detected by SPECT scanning in HIV-infected patients. However, further studies are needed to evaluate the clinical significance and to develop possible therapeutic consequences.